Effects of epidemic diseases on the distribution of bonobos. - Bila-Isia Inogwabini (Public Library of Science (PLoS), 2012)
This study examined how outbreaks and the occurrence of Anthrax, Ebola, Monkeypox and Trypanosomiasis may differentially affect the distribution of bonobos (Pan paniscus). Using a combination of mapping, Jaccard overlapping coefficients and binary regressions, the study determined how each disease correlated with the extent of occurrence of, and the areas occupied by, bonobos. Anthrax has only been reported to occur outside the range of bonobos and so was not considered further. Ebola, Monkeypox and Trypanosomiasis were each reported within the area of occupancy of bonobos. Their respective overlap coefficients were: J = 0.10; Q(α = 0.05) = 2.00 (odds ratios = 0.0001, 95% CI = 0.0057; Z = -19.41, significant) for Ebola; J = 1.00; Q(α = 0.05) = 24.0 (odds ratios = 1.504, 95% CI = 0.5066-2.6122) for Monkeypox; and, J = 0.33; Q(α = 0.05) = 11.5 (Z = 1.14, significant) for Trypanosomiasis. There were significant relationships for the presence and absence of Monkeypox and Trypanosomiasis and the known extent of occurrence of bonobos, based on the equations y = 0.2368Ln(x)+0.8006 (R(2) = 0.9772) and y = -0.2942Ln(x)+0.7155 (R(2) = 0.698), respectively. The positive relationship suggested that bonobos tolerated the presence of Monkeypox. In contrast, the significant negative coefficient suggested that bonobos were absent in areas where Trypanosomiasis is endemic. Our results suggest that large rivers may have prevented Ebola from spreading into the range of bonobos. Meanwhile, Trypanosomiasis has been recorded among humans within the area of occurrence of bonobos, and appears the most important disease in shaping the area of occupancy of bonobos within their overall extent of occupancy.